How Universal is the Youth Crime Drop? Disentangling Recent Trends in Youth Offending through a Socio-Economic Lens - McCarthy, Molly (Victims & offenders, 2021)
Recent research has consistently found declines in youth offending, and it has been suggested that youth offending may have become more concentrated in lower socio-economic communities. However, there has been limited empirical examination of this proposition. This study aimed to examine changes in the relative concentration of youth offending in low and high socio-economic communities in an Australian jurisdiction, from 2008 to 2018, and to explore socio-economic drivers of different types of youth offending over this period. Changes in offending concentration were measured using ratios of youth offending rates in low and high socio-economic communities over time and Poisson panel regression was used to explore socio-economic drivers of youth offending rates. Findings indicated disparate patterns across youth offending types, with significant decreases in one-off and low to moderate offending, and significant increases in chronic offending over the same period. Overall, youth offending was not found to have become increasingly concentrated in lower socio-economic communities, primarily due to larger relative increases in chronic offending in higher socio-economic communities. Despite a slight decrease in concentration, lower socio-economic communities continue to experience markedly higher youth offending rates. Findings indicate a need to better understand drivers of recent increases in chronic youth offending.